TLKHYS ALTJRYD L’EMDH ALMRYD SHRH JWHRH ALTWHYD IMAM IBRAHIM ALLAQANY–MANUSCRIPT (388) TO (389) - Anbar University (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Praise be to God, Lord of the worlds, and the best of prayers and blessings be upon our prophet Muhammad and his family and companions. Now to our topic, the science of (tawheed) monotheism is one of the most important sciences that a person must learn. A great science deals with the principal issues of man on this earth like the divinity of God Almighty mission reward and punishment in the hereafter. Scholars of this science form the scientific defense front and they are able to fend off false beliefs and refute suspicions, the researcher aims at shedding the light nobly ona doctrine book entitled “Tlkhys altjryd l'emdh almryd shrh jwhraltwhyd Imam Ibrahim Allaqany – manuscript (388)to (389)”.VersionAis selected to study for two reasons: it is hand-written by the author himself and it is the most obvious version. The researcher supplicate Allah for aid and power to sail into the lines of this manuscript.